Booker T. Washington Papers Volume 8 : 1904-6. Assistant editor, Geraldine McTigue - Washington, Booker T., 1856-1915 (Book collections on Project MUSE., 2015)
Fame and influence far beyond that accorded any other black leader of the period continued to bolster Booker T. Washington's career in the two years covered by the most recent volume in this major project in black history. Volume 8 finds the Tuskegean becoming more and more a national figure, consolidating his position as presidential adviser and patronage broker, while still trying to quell black opposition to his leadership. Various letters catalog his ability to direct political "plums," to thwart the organization of potentially threatening groups, and to gain more honors for himself.